Sistema de detección y reconocimiento de falla en un tipo de tarjeta electrónica de celulares motorola - Betancourt Uscátegui, Álvaro; Rojas, Alexander; Diaz, Sergio (Ingeniería, 2003)
This paper describes a system for detection and pattern recognition of corrosion using the artificial vision computation in motorola cellular telephones. The corrosion produces an automatic degradation of internal joints of the circuit board causing multiple failures. Due to the absence of tools to permit the perfect analysis and inspection of the circuit board,the failure is not always detected. This developed system corrects this problem.